Phase and thermal diffusivity variation of saline water diagnosed by visual and temperature method during freezing process - Shih-Chang Huang; Chin-Chi Cheng; Hong-Ping Cheng (Results in Engineering)
Freezing step is a fundamental physical phenomenon of cooling a liquid formulation for guaranteeing product quality. In this study, freezing process of saline water under various concentrations was monitored through the visual and temperature methods. The formation of the ice crystal nuclei at the supercooling stage, and the increase of ice and ice/water layers were observed. The formation of the ice crystal nuclei and ice layer was affected by the location of vials placed on a shelf and the concentration of saline water. A saline water solution at a higher concentration had a lower ice layer height under the same freezing settings. The location of vial on the shelf affects the stability and efficiency of thermal transmission. Moreover, the concentration of saline water has the relationship with the thermal diffusivity, and ice layer is an indicator of variation of temperature and thermal diffusivity for saline water during freezing process. This study was able to replicate and observe the physical phenomena of the formation of ice crystal nuclei and the ice layer during the freezing process under laboratory conditions; as well as show how the specific concentration of the saline water solution affected the developmental speed of the ice layer.